The Impact of the COVID-19 Pandemic on Neonatal Health Outcomes in Sub-Saharan Africa: A Targeted Investigation of Medical Records in Kinshasa, Democratic Republic of the Congo with an Expansive Meta-Analysis Among Sub-Saharan Countries - Arena, Patrick Joseph (ProQuest Dissertations & Theses, 2023)
Despite advances in maternal and neonatal health over the past few decades, a disproportionate amount of adverse birth outcomes (e.g., stillbirth, low birth weight [LBW], and preterm birth [PTB]) still occur in low- and middle-income countries. In the Democratic Republic of the Congo (DRC), health officials have been exploring ways to expand pharmacovigilance (PV) capabilities for the detection of adverse maternal and neonatal health outcomes and also striving to learn more about the impact of the COVID-19 pandemic on neonatal health outcomes. In response, this dissertation utilized a PV study – conducted from July 1, 2019 to January 31, 2021 in Kinshasa, DRC – in conjunction with external surveillance data and data from the literature to address these subjects. Chapter 1 provides a broad summary of the current state of maternal and neonatal health both generally and in the context of the DRC. Chapter 2 assesses the equivalency of alternative data sources (in the form of archival medical records and enhanced monitoring data) to external surveillance data for the detection of maternal and neonatal health outcomes; the results generally indicated that such alternative data sources could serve as suitable PV tools for the monitoring of adverse birth outcomes in Kinshasa, DRC. Chapter 3 utilizes natural experimental methods to investigate the impact of the COVID-19 pandemic on selected neonatal health outcomes; the results revealed that the stillbirth rate appeared to remain stable while the LBW and PTB rates seemed to decline slightly after the imposition of COVID-19 mitigation measures in Kinshasa, DRC. Chapter 4 employs systematic review and meta-analysis methodology to examine the relationship between COVID-19 mitigation measures and neonatal health outcomes in sub-Saharan Africa; despite issues concerning high heterogeneity, the results generally suggested no change in stillbirth, LBW, or PTB after the imposition of COVID-19 mitigation measures among multi-national/national/regional studies but also highlighted the need for further research within sub-Saharan African countries. Chapter 5 provides a high-level summary and implications for future research and public health. Overall, this dissertation provides insights on solutions for PV systems strengthening for the benefit of maternal and neonatal health outcomes and offers additional perspectives on the impact of the COVID-19 pandemic on neonatal health outcomes within the context of the DRC specifically and sub-Saharan Africa more generally.